Literatur Riview : Analisis Pengendalian Persediaan Bahan Baku Dengan Menggunakan Metode Economic Order Quantity (EOQ) (Studi kasus Perusahaan di Indonesia) - alia candra devi; Reynalda Suryono; Riska Ristiana; Riski Febriyanti; Ujang Suherman (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to investigate Production Planning and Inventory Control of Raw Materials in Indonesian companies through a relevant literature review. The article discusses the analysis of raw material inventory control using the Economic Order Quantity (EOQ) method based on case studies in several Indonesian companies. Efficient inventory is essential to support smooth production and sales processes, ensure customer satisfaction, and avoid inefficient storage costs. The EOQ method is the main focus of this research, considering storage and ordering costs to achieve an optimal order quantity. Through systematic literature review, this article evaluates various studies related to raw material inventory control using the EOQ method. The research findings indicate that implementing EOQ in companies such as PT. Suryamas Lestari Prima, Prizel Perak Bali, PT. XYZ, PT. Global Mulia Nusantara, PT. Budi Starch & Sweetener, Tbk, and PT. Pratama can result in cost savings, determine optimal order quantities, and improve ordering frequency efficiency. In conclusion, the use of the EOQ method contributes positively to the efficiency and effectiveness of raw material inventory control in various manufacturing companies in Indonesia.